A rare case of silicosis with hepatitis B infection. (December 2022) - Shrestha, A.B.; Yadav, A.K.; Shrestha, S.; Shrestha, S.R.; Shrestha, S.; Yadav, H.R.; Shrestha, S.
Abstract: Introduction: Silicosis is a type of diffuse interstitial lung disease caused by inhalation of crystalline silicon dioxide. The number of silicosis cases have been rapidly increasing over the years. Complete cure is not possible so early diagnosis and prevention is required. Case presentation: Our patient came with chief complaints of productive cough, breathlessness progressing to MRC grade 4 and fever. He worked in a flour mill for 15 years and has been symptomatic for the past 4–5 years. Chest examination showed tracheal deviation to the right, bilateral decreased breath sounds and fine crepitations. Chest X ray showed multiple tiny nodular opacities in all lung zones. Pulmonary function test confirmed restrictive lung disease. On CT scan, miliary mottled densities were noted bilaterally along with fibrosis in upper lobes and ground glass appearance in lower lobes. Echocardiography revealed mild pericardial effusion and Abdominal Ultrasound revealed coarse liver texture, splenomegaly and right sided pleural effusion. Patient was also Hepatitis B positive.Patient was treated with Prednisolone, Entecavir, Moxaclav along with symptomatic management. Discussion: Male gender, HIV infection, Smoking, Occupation, Age at first exposure, Duration of exposure and Concentration of inhaled silica dust are the risk factors of silicosis. Individuals with Silicosis are at high risk of developing Tuberculosis and Hepatitis B infection. Pulmonary function test, HRCT and Lung biopsies help in diagnosis of Silicosis. Serological markers and Liver Function Test helps in diagnosis of Hepatitis B infection. Early diagnosis and prevention is essential for better prognosis and Lung transplant is the only definitive management. Complications like progressive fibrosis, infections, cor pulmonale and pneumothorax may result due to Silicosis. Conclusion: Silicosis is a rare chronic inflammatory condition which leads to an immunosuppressed state and may predispose individuals to opportunistic conditions like Hepatitis B. Therefore, early identification of risk factors and clinical features is required. Highlights: An occupational disease that may not decrease life expectancy but results in severe lifelong morbidity. Immunosuppressed state predisposing an individual to a variety of medical complications. Requires lifelong management and a higher prevalence among people of lower income posing a significant burden of disease.